Electrochromic devices incorporating biohybrid electrolytes doped with a lithium salt, an ionic liquid or a mixture of both. (10th April 2015) - Fernandes, M.; Leones, R.; Costa, A.M.S.; Silva, M.M.; Pereira, S.; Mano, J.F.; Fortunato, E.; Rego, R.; de Zea Bermudez, V.
Graphical abstract: Highlights: Poly(ϵ-caprolactone)/siloxane biohybrid electrolytes were prepared by sol-gel chemistry. The electrolytes were doped with LiCF3 SO3, an IL or the mixture of both. The IL used was 1-ethyl-3-methyl imidazolium tetrafluoroborate ([Emim]BF4 ). Prototype electrochromic devices incorporating the three electrolytes were tested. Abstract: The sol-gel method was employed in the synthesis of di-urethane cross-linked poly(ϵ-caprolactone) (PCL(530))/siloxane biohybrid ormolytes incorporating either a mixture of lithium triflate (LiCF3 SO3 ) and the ionic liquid (IL) 1-ethyl-3-methyl imidazolium tetrafluoroborate ([Emim]BF4 ), or solely with [Emim]BF4 or LiCF3 SO3 . The ormolyte doped with [Emim]BF4 is thermally more stable and exhibits higher ionic conductivity (4 × 10 −4 and 2 × 10 −3 S cm −1 at 36 and 98 °C, respectively) than those containing the LiCF3 SO3 /[Emim]BF4 mixture or just LiCF3 SO3 . The three ormolytes were employed in the production of glass/ITO/ormolyte/WO3 /ITO/glass electrochromic devices (ECDs) designated as ECD@Y with Y = Li-[Emim]BF4, [Emim]BF4 and Li. The three ECDs displayed fast switching speed (ca. 30 s). ECD@Li-[Emim]BF4 exhibited an electrochromic contrast of 18.4% and an optical density change of 0.11 in the visible region, the coloration efficiency attained at 555 nm was 152 and 80.2 cm 2 C −1 in the "on" and "off" states, respectively, and the open circuit memory was 48 hours. In the "on" state the CIE 1931 color space coordinates were x = 0.29 and y = 0.30, corresponding to blue color.